Studies of polymer surface topography by means of optical profilometry - Jaglarz, Janusz; Sanetra, Jerzy; Cisowski, Jan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The optical reflection measurements of polyvinylocarbazole (PVK) and polyazomethine (PPI) thin films have been done by means of optical profilometry (OP) exhibiting many advantages in surface and subsurface investigations. The obtained OP images clearly demonstrate that the thickness of the polymer films under investigation is not uniform over their lateral dimensions. For the PVK thin film, the fast Fourier transform (FFT) in the inverse space of the OP image is also presented along with distribution of the surface highs.
Optica Applicata, Vol. 40, 2010, nr 4, s. 767-772
Keywords: optyka; optical profilometry; thin polymeric films